Povidone-iodine bowel irrigation before resection of colorectal carcinoma. - Parker, M. C. (Royal College of Surgeons of England, 1985)
Preoperative mechanical bowel preparation, peroperative topical antiseptic measures, and postoperative antibiotic therapy have all been shown to reduce infection after colorectal surgery. We report the results of a randomised trial of preoperative irrigation with a 10% aqueous solution of povidone-iodine (Betadine) versus water in patients undergoing major resection for large bowel carcinoma. All patients had mechanical bowel preparation, preoperative topical povidone-iodine and per and postoperative antibiotics. Of 22 study patients only one (4.6%) developed abdominal wound infection, whereas in 23 controls nine (39.1%) did so (P less than 0.01). In three of the study patients cultures of swabs taken at operation from the transected bowel ends showed no bacterial growth. Arguably the bacterial population would have been markedly reduced in other patients. These results suggest that povidone-iodine irrigation before large bowel resection reduces wound sepsis.